Assessing Prejudice Toward Two-Father Parenting and Two-Mother Parenting: The Beliefs on Same-Sex Parenting Scale. Issue 4 (13th June 2018) - Ioverno, Salvatore; Carone, Nicola; Lingiardi, Vittorio; Nardelli, Nicola; Pagone, Paolo; Pistella, Jessica; Salvati, Marco; Simonelli, Alessandra; Baiocco, Roberto
Abstract : This article describes two interrelated studies that investigated beliefs and stereotypes on two-father parenting and two-mother parenting through the development and validation of the Beliefs on Same-Sex Parenting (BOSSP) scale. The BOSSP captures two beliefs: (1) prejudices toward same-sex couples' inherent inability to parent and (2) concerns about same-sex parenting that are not necessarily related to homonegativity. In Study 1 (301 heterosexual participants), exploratory factor analysis (EFA) suggested an 11-item scale for attitudes toward both two-father families and two-mother families, with two factors: parenting skills, which evaluates beliefs on same-sex couples' ability to take care of their children; and parental adjustment, which assesses beliefs on the impact of challenges related to same-sex parenting on children's well-being. Support for convergent validity between BOSSP factor scores and those of theoretically related measures were provided. In Study 2 (346 heterosexual participants surveyed in two time points), CFA indicated that the two-factor model provided the best fit. Test-retest reliability and longitudinal invariance were documented. Finally, results revealed that more negative attitudes toward same-sex parenting were held by men than by women and were associated with negative opinions on reproductive techniques. The innovative characteristics of the BOSSP and implications for future practice are discussed.